2018
DOI: 10.1016/j.ihj.2018.10.410
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and predictors of depression in congestive heart failure

Abstract: BackgroundDepression in congestive heart failure (CHF) patients can increase morbidity and mortality. Given the ever-rising prevalence of CHF patients with depression, it is vital that we understand the predictors of depression in these patients to identify and better manage these patients. The main objective of this study was to evaluate the frequency and predictors of depression in CHF patients.MethodsA cross-sectional study was conducted in a tertiary care hospital. Patients with a diagnosis of CHF for more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
35
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 44 publications
5
35
1
1
Order By: Relevance
“…The higher prevalence of depression in our patients is likely influenced by educational and socioeconomic factors that are unique to populations in middle income countries. This hypothesis is supported by a study conducted in Pakistan, where the prevalence of depression in 170 patients with CHF was found to be 60% [8].…”
Section: Discussionmentioning
confidence: 64%
“…The higher prevalence of depression in our patients is likely influenced by educational and socioeconomic factors that are unique to populations in middle income countries. This hypothesis is supported by a study conducted in Pakistan, where the prevalence of depression in 170 patients with CHF was found to be 60% [8].…”
Section: Discussionmentioning
confidence: 64%
“…The higher prevalence of symptoms of depression in our patients is likely in uenced by socioeconomic factors unique to populations in LMIC. This hypothesis is supported by a study conducted in Pakistan, where the prevalence of depression in 170 patients with CHF was found to be 60% [13].…”
Section: Discussionmentioning
confidence: 64%
“…The majority of patients with heart disease were elderly and felt that they had done tasks for their children and their families, so they do not have that burden associated with it, the opposite occurred in patients with heart disease at a younger age, they thought they still have a duty to be fulfilled, this can worsen their psychosocial conditions [14]. However, these results differ from studies conducted in Pakistan which showed that age was not related to BDI (depression) scores [8] and research conducted by Zahid et al (2018), which stated that age over 70 years was one predictor of depression [13].…”
Section: Discussionmentioning
confidence: 88%
“…The cause of the high proportion of depression in this study is uncertain. However, this might be possible as a result of other factors not analyzed in this study, including the high level of NYHA classification, poor lifestyle [13], a higher symptom burden and low social support [7].…”
Section: Discussionmentioning
confidence: 99%